Pengaruh Penggunaan Media Pop Up Book Terhadap Kemampuan Membaca Anak di TK Insan Cita Kec. Masamba Kab. Luwu Utara - Hajerah Hajerah; Syamsuardi Syamsuardi (Seminar Nasional LP2M UNM, 2019)
Abstract. The problem of this research were: (1) how is the description of the implementation media pop up book in TK Insan Cita Kelurahan Bone Kecamatan Masamba Kabupaten Luwu Utara? (2) how is the description of children’s linguistic intellegence before and after using the media pop up book in TK Insan Cita Kelurahan Bone Kecamatan Masamba Kabupaten Luwu Utara (3) is there an influence of the use of pop up book media on chilndren’s linguistic intellegence in TK Insan Cita Kelurahan Bone Kecamatan Masamba Kabupaten Luwu Utara? The aims of this research were (1) to find out the description of using the media pop up book implementation in TK Insan Cita Kelurahan Bone Kecamatan Masamba Kabupaten Luwu Utara; (2) the description og children’s linguistic intelegence befor and after using the media pop up book implementation in in TK Insan Cita Kelurahan Bone Kecamatan Masamba Kabupaten Luwu Utara; (3) to know influence of the use of pop up book media on chindren. The kind of this research is pre eksperimental designe. The population are 21 and the sample is 11. The result showed a comparison between the value of Thitung < Ttabel using a signicance value of 05, the conclusion, value of 0,05 that means Ho was rejected. This means learning methods using using pop up media has an influence on aspect of development epecially aspek of language development Keywords: Pop up book, linguistics